PEMBERDAYAAN DAN SINERGITAS ORANGTUA DALAM MEMOTIVASI BELAJAR ANAK USIA SEKOLAH DI DESA PUNCAKSARI BANDUNG BARAT : Pemberdayaan Motivasi Belajar - Murharyana Murharyana (Jurnal Al Maesarah, 2023)
Implementation of Darul Falah STAI Field Work Lecture in Puncaksari Village, West Bandung has the goal of changing the mindset of parents and children in improving formal education and religious education. Facts in the field of the residents of the Puncaksari village regarding their views about the importance of an education are still below average, it was found that there were problems with continuing education strata for children during their study period which only finished at the age of 9 years at junior high school level) after they got married, worked. Parents for their children think that education is enough to be able to read and count then work, wander and try their luck, this happens based on economic factors. Through the implementation of Real Work Lectures, students, supervisors and in collaboration with the local government are trying to provide input and views related to the importance of a continuous formal education and religious education in the environment they live in, this is material for raising the dignity of families and communities through education. The actions carried out from the real work lecture program were in the form of facilitating them with educational activities such as counseling, talent and art competitions, establishing a mini village library, and verbal motivation about the enthusiasm for learning. The result of this implementation is that the enthusiasm for learning of the children in the Puncaksari village is increasing as seen by their active participation in the activities carried out in the KKN program, besides that words of happiness can be heard from their parents when children have talents and competencies which are facilitated by KKN participants.